2021
DOI: 10.3390/agronomy11030452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Presence of Grape Skins during White Wine Alcoholic Fermentation

Abstract: The production of white wines with the presence of grape skins is a historical technique used in different regions with winemaking tradition. However, the current trend is to maintain the presence of grape skins during white wine making only during the pre-fermentation phase in order to enrich and give greater complexity to the sensory profile of the wines. Given these precedents, this study is the first to consider the effect of the presence of different grape skins doses throughout the alcoholic fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
8
18
0
1
Order By: Relevance
“…In this sense, control wines with GS presence showed a 27.7% and 25.1% higher population for the 2018 and 2019 vintages, respectively. In the same way and coinciding with the results of recently published research papers, it is confirmed that the presence of a certain amount of GS is able to sponsor a greater growth and survival of yeasts [ 33 ]. This may possibly be due to the presence of nitrogen compounds and other growth cofactors necessary for yeast growth found in grape skins [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In this sense, control wines with GS presence showed a 27.7% and 25.1% higher population for the 2018 and 2019 vintages, respectively. In the same way and coinciding with the results of recently published research papers, it is confirmed that the presence of a certain amount of GS is able to sponsor a greater growth and survival of yeasts [ 33 ]. This may possibly be due to the presence of nitrogen compounds and other growth cofactors necessary for yeast growth found in grape skins [ 52 , 53 ].…”
Section: Resultssupporting
confidence: 84%
“…However, significant differences (ANOVA p < 0.05) were only observed for the CH96h samples, where the fermentation rate was higher. Nevertheless, for the rest of the samples, no major differences in fermentation kinetics were detected, coinciding with the recent results of the research group, a higher proportion of GS being necessary to significantly accelerate the fermentation process [33]. Finally, none of the samples during the two vintages studied presented problems in the final phase of fermentation, which could be carried out correctly until the end.…”
Section: Effect Of Over-ripening and Grape Skin (Gs) Presence During Alcoholic Fermentationsupporting
confidence: 85%
See 3 more Smart Citations